The Effect of Adding Generation Bus to the Short Circuit Current Level in Electrical Power System - Ayu Elsa Afriyanti; Muhammad Imran Hamid; Anna Cyntia Pahsa De Yudanur; Niko Saputra (Andalas Journal of Electrical and Electronic Engineering Technology, 2025)
The need for electrical energy is changing and increasing, requiring system flexibility always to be changed and developed. On the other hand, changes in the configuration of the electric power system due to the addition of components or sub-systems also change system parameters such as impedance or level of fault current (short circuit current). This paper presents a study of changes in the fault current caused by adding a new generating bus to an electric power system. This paper aims to determine the change in short-circuit current due to the addition of generators on new buses connected to existing buses to identify the most suitable location for adding these generators based on short-circuit current levels. Three-phase short circuit faults are simulated and analyzed on the IEEE 14 bus standard system using ETAP software with a base MVA 615 MVA. The addition of generators was carried out at five locations with varying generating capacities. The research results show that the short circuit current will change significantly when adding a generator bus to bus 13, with an average percentage change of 5,656%. The smallest change occurs when adding a generator to bus 2, with an average percentage change of 2,417%. The research results conclude that connecting a generator to a new bus linked to an existing generator bus (PV bus) is more effective than connecting it to a new bus associated with a load bus (PQ bus).